Dopamine triggers TOR signaling cascade to drive biomass and astaxanthin hyperaccumulation in Haematococcus lacustris under coordinated salinity and gradient light stress - Shiyu Lin; Qingwei Wang; Raoqiong Che; Qingqing Li; Chunli Yu; Min Yang; Lifang Li; Penghua Gao; Ying Qi; Feiyan Huang; Xiang Wang; Yongteng Zhao; et al. (Bioresource Technology, 2026)

Fruit allergens and their allergenicity reduction: characteristics, technologies, and prospects - Tanying Zhang; Jinshen Chu; Yuntong Ying; Haochen Ye; Mengxian Li; Yiran Xie; Haozhe Yi; Jing Che; Bowen Li; Binjia Zhang; Xiaowen Pi (Trends in Food Science & Technology, 2026)

Devonian Jinshuikou pegmatites at the northern margin of the Tibetan Plateau: UPb and SmNd constraints on their genetic relationship with regional granitoids - Si-Qi Liu; Shao-Yong Jiang; Mostafa Fayek; Hui-Min Su; Yu-Ying Che; Wei Wang; Qinglin Xia (Lithos, 2026)

Ventilation and air conditioning design for interconnected large-space underground pumped storage power stations and prediction method for spatial temperature distribution - Lianhua Deng; Jigang Che; Angui Li; Shaofeng Niu; Jing Xiong; Ying Zhang (Building and Environment, 2026)

Chlorpyrifos exposure induces inflammatory and immune dysregulation: An integrative in silico and in vitro analysis - Chen-Yu Chiang; Shih-Pin Chen; Ci-Wen Luo; Chun-Hung Su; Shiuan-Shinn Lee; Wen-Ying Chen; Chun-Jung Chen; Ching-Chi Tseng; Pin-Tzu Chen; Yin-Che Lu; Yu-Hsiang Kuan (Pesticide Biochemistry and Physiology, 2026)

A circular “capture-and-upcycle” strategy for micro/nano-plastic remediation: From aquatic pollutants to fire-safe composites - Zhuo Huang; Jiawei Ying; Long Liu; Jiantao Zheng; Youming Yu; Wenhui Bao; Wenbo Che (Journal of Hazardous Materials, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Global disparities in 3D urban morphology shaped by building height and distributions - Yangzi Che; Xuecao Li; Ying Wu; Yucong Sun; Bingjie Li; Xiaoping Liu (Science Bulletin, 2026)

Distribution characteristics and potential microbial degradation mechanisms of microplastics in oyster aquaculture areas of southern China - Hui Zhao; Wenxue Che; Xiao Tan; Yuhan Shen; Yue Xu; Ying Man (Journal of Hazardous Materials, 2026)

Insight into influencing factors and simulating models of migration, potential hazards, and analytic technology on microplastic in agricultural soil - Che Zhao; Xixi Lian; Yazhuo Wang; Ying Gu; Dong Liang (Journal of Environmental Sciences, 2026)

Regulatory patterns and driving factors of soil aggregates on the environmental behavior of heavy metals: A global study based on meta-analysis and machine learning - Yu-Xuan Song; Yuhan Meng; Bingxuan Zhao; Tian-Hao Che; Zining Li; Zuozhou Yu; Xinyang Zhen; Yining Li; Chengyong Li; Quan-Ying Wang; Jing-Ya Zhou (Environmental Geochemistry and Health, 2026)

Strategic directions for mitigating cultivated soil acidification in China: Insights from global progress and local practice - Ren Fang SHEN; Ying TENG; Jing CHE; Xueqiang ZHAO (Pedosphere, 2026)

ATP-citrate lyase is a critical regulator of physiological and pathological angiogenesis - Chong Xu; Ying Lin; Zeyu Wang; Cailin Feng; Lingfeng Luo; Shuai Guo; Han Zhang; Lu Liu; Azhen Fan; Penglong Qi; Dongyang Jiang; Yiming Xu; et al. (Angiogenesis, 2026)

Quality enhancement of frozen dough steamed bread by Sanxan: A study on multi-stage regulation of gluten-starch matrix - Haojia Zhu; Heqiao Qian; Jie Li; Hanzhang Hao; Ying Huang; Shenying Zhang; Yingxue Che; Mei Liu; Ying Liang; Xueling Zheng; Chong Liu; Limin Li (Food Hydrocolloids, 2026)

Synergistic activation of peracetic acid by carbon-confined CoFe2O4 microspheres for efficient levofloxacin degradation: Dominant role of acetylperoxy radicals and singlet oxygen - Ying Yang; Xinrong Che; Tianyue Gao; Siyuan Jiang; Jianfeng Gou; Xiuwen Cheng (Journal of Environmental Chemical Engineering, 2026)

Effects of recombinant carrot antifreeze protein concentrations on frozen dough and bread: Insights into dynamic changes of water and ice crystals - Ying Huang; Shenying Zhang; Haojia Zhu; Caiyun Liu; Zichen Huang; Hanzhang Hao; Yingxue Che; Mei Liu; Ying Liang; Xueling Zheng; Chong Liu; Limin Li (Food Chemistry, 2026)

Experimental and numerical investigations of heavy gas leakage in long and narrow spaces - Yuanqing Ma; Angui Li; Tianqi Wang; Ying Zhang; Changqing Yang; Jigang Che; Yifan Wang; Dingmeng Wu (Building and Environment, 2026)

Evaluation of salt tolerance in Agropyron Gaertn.: key indicators, optimal conditions, and implications for crop improvement - Jiarui Zou; Jing Yang; Ying Liu; Yanping Yang; Lai Wei; Haiming Han; Shenghui Zhou; Weihua Liu; Jinpeng Zhang; Lihui Li; Yonghe Che (Genetic Resources and Crop Evolution, 2026)

Integrating structural equation modeling and machine learning to unravel the drivers of fine-grained urban thermal patterns - Ying Ding; Chen Huang; Jue-Yu Lin; De-Shun Xu; Yang-Zi Che; Ying Sun; Wei-Lin Liao (Urban Climate, 2025)

Chromosome-level genome assembly reveals divergent immune mechanisms in the genus Meretrix - Che-Chun Chen; Te-Hua Hsu; Hsin-Yun Lu; Sen-Lin Tang; Ying-Ning Ho (Fish & Shellfish Immunology, 2025)

Investigate the protective effects of eicosapentaenoic acid in human astrocytes of oxidative stress damage and explore its underlying mechanisms - Che-Sheng Chu; Ying-Tso Chen; Wei-Chih Sun; Wei-Zhe Liang (Molecular Biology Reports, 2025)

Outbreeding of isofemale lines as a candidate approach to improve the quality of thelytokous Wolbachia-infected line of the egg parasitoid, Trichogramma dendrolimi Matsumura (Hymenoptera: Trichogrammatidae - Hong-Yu Liang; Ying Shan; Qian-Jin Dong; Jin-Cheng Zhou; Xiao-Hui Ma; Li-Sheng Zhang; Wu-Nan Che; Hui Dong (Journal of Invertebrate Pathology, 2025)

Investigation of the impact of local tumor phenolic-chemistry for dual starvation and vaccination therapy - Jingsong Lu; Zhenhu Guo; Sumei Chen; Ying Li; Xin Xu; Jing Yu; Shenglei Che; Guifeng Zhang; Wensheng Xie; Yen Wei; Lingyun Zhao (Chemical Engineering Journal, 2025)

Interactions between turnover rate and bioactivity of atractylenolide III in Atractylodes macrocephala rhizome in the theory of crude drugs’ pairs and prescriptions in traditional Chinese and Japanese Kampo medicine - Pei-Ying Chou; Yung-Jia Chiu; Che-Chun Lin; Lih-Geeng Chen; Shih-Yi Hsiung; Toshiaki Makino; Ching-Chiung Wang (Journal of Natural Medicines, 2025)

Urinary phthalate metabolites associate with blood levels of estrogen quinone-derived hemoglobin adducts in Taiwanese pregnant women - Shu-Li Wang; Dar-Ren Chen; Sheng-Yen Hsu; Chia-Wei Liu; Che Lin; Chien-Wen Sun; Pen-Hua Su; Ying-Chih Tseng; Po-Hsiung Lin (Toxicology Letters, 2025)

Graft-modified amphiphilic dendron/polyimide regular through-pore composite membranes for oil/water separation - Chien-Chieh Hu; Cai-Syuan Sung; Ru-Jong Jeng; Chien-Hsin Wu; Ying-Chi Huang; Huai-Che Chang; Kueir-Rarn Lee; Juin-Yih Lai (Chemical Engineering Journal, 2025)

Biopolymer-amended geosynthetic clay liners for landfills and contaminated sites: Gas and hydraulic performance - Ying-Zhen Li; Heng Zhuang; Ji-Ying Fan; Wei-Yi Xia; Jia-Lei Wan; Chi Che; Yan-Jun Du (Environmental Research, 2025)

Enhanced complexity of interkingdom co-occurrence networks in blueberry rhizosphere microbial communities under soil pH stress - Jilu Che; Yaqiong Wu; Hao Yang; Ying Chang; Wenlong Wu; Lianfei Lyu; Xiaomin Wang; Fuliang Cao; Weilin Li (Applied Soil Ecology, 2025)

Novel synthesis and application of biochar for controlling release and exposure of mercury in the farmland: From human health risk perspective - Nathan Thadeo Yoashi; Che-Jung Hsu; Ying-Lin Wang; Po-Hui Wu; Zheng-Yei Hseu; Ling-Chu Chien; Hsing-Cheng Hsi (Environmental Research, 2025)

Investigating the impact of fecal contamination on antibiotic resistance genes in urban environments using host-associated molecular indicators - Yujing Duan; Hui She; Lingna Jing; Lianrui Duan; Jinxiu Zheng; Ying Shao; Yuxin Che; Yu Shi; Chao Guo; Wenhui Zhao; Tao Yang; Lijun Yang (Environmental Pollution, 2025)

A multi-source data-driven innovative evaluation approach for assessing low-carbon city performance - Xiaoyun Du; Zhijie Li; Yingna Gao; Ying Che (Sustainable Cities and Society, 2025)

Spatial characteristics of microbial communities and their functions in sediments of subtropical Beibu Gulf, China - Wenxue Che; Hui Zhao; Ying Man; Xiao Tan (Marine Environmental Research, 2025)

Single-step pyrolytic synthesis of ultra-microporous ammonialized biochar for carbon dioxide capture - Che-Jung Hsu; I-Lin Kuo; Hsing-Cheng Hsi; Su Shiung Lam; Ying-Pin Huang; Yu-Chieh Ting (Journal of Environmental Management, 2025)

Mercury pollution control and Marphysa sanguinea bio-response in active-capped sediment with calcium alginate/activated carbon composite - Che-Jung Hsu; Ying-Chu Wang; Adrienne Chung; Cheng-Di Dong; Chiu-Wen Chen; Yu Ting; Hsing-Cheng Hsi (Journal of Hazardous Materials, 2025)

Development and characterization of novel wood-based composite materials for solar-powered atmospheric water harvesting: A machine intelligence supported approach - Xingying Zhang; Yangyang Xu; Shenjie Han; Xiang Weng; Wenbo Che; Kongjie Gu; Ying Guan; Youming Yu; Derek Hao; Junfeng Hou (Journal of Cleaner Production, 2025)

Revealing the mechanisms of rhamnolipid enhancing methane production from anaerobic digestion of bituminous coal - Shufeng Zhao; Hongyu Guo; Norbert Klitzsch; Daping Xia; Xiao Liu; Yan Liu; Ying Che (Biomass and Bioenergy, 2025)

The impact of urban morphology on land surface temperature across urban-rural gradients in the Pearl River Delta, China - Ying Wu; Yangzi Che; Weilin Liao; Xiaoping Liu (Building and Environment, 2025)

Impacts of micro/nano plastics on the ecotoxicological effects of antibiotics in agricultural soil: A comprehensive study based on meta-analysis and machine learning prediction - Tian-Hao Che; Guan-Kai Qiu; Hong-Wen Yu; Quan-Ying Wang (Science of The Total Environment, 2024)

Copper/iron bimetal phenolic networks boosted apoptosis/ferroptosis/cuproptosis combined tumor therapy through dual glutathione depletion - Fan Zhao; Hongyan Yu; Chen Wang; Junchen Xu; Hao Gao; Yao Ying; Wangchang Li; Juan Li; Jingwu Zheng; Liang Qiao; Shenglei Che; Jing Yu (Chemical Engineering Journal, 2024)

Accurately estimate soybean growth stages from UAV imagery by accounting for spatial heterogeneity and climate factors across multiple environments - Yingpu Che; Yongzhe Gu; Dong Bai; Delin Li; Jindong Li; Chaosen Zhao; Qiang Wang; Hongmei Qiu; Wen Huang; Chunyan Yang; Qingsong Zhao; Like Liu; et al. (Computers and Electronics in Agriculture, 2024)

Metabolites of blueberry roots at different developmental stages strongly shape microbial community structure and intra-kingdom interactions at the root-soil interface - Jilu Che; Yaqiong Wu; Hao Yang; Ying Chang; Wenlong Wu; Lianfei Lyu; Xiaomin Wang; Fuliang Cao; Weilin Li (Science of The Total Environment, 2024)

Scale-dependent effects of vegetation attributes and soil fertility on productivity in two temperate forests in Northeast China - Ying Che; Huiying Cai; Guangze Jin (CATENA, 2024)

Nondestructive estimation of specific macroelement contents in thalli of the red macroalga Pyropia yezoensis using hyperspectral imaging - Shuai Che; Lan Wu; Zhen-Dong Wang; Lin Tian; Guo-Ying Du; Yun-Xiang Mao (Journal of Applied Phycology, 2024)

Formation of conjugated polymer/TiO2(B) S-scheme heterojunctions by functional group regulation for efficient natural light-driven inactivation of super-resistant bacteria - Xin Zhao; Simiao Wang; Diyang Shan; Ying Xu; Lina Wu; Haiyong Guo; Guangbo Che; Chunbo Liu; Juan Du (Chemical Engineering Journal, 2024)

Exploring the biphasic dose-response effects of photobiomodulation on the viability, migration, and extracellular vesicle secretion of human adipose mesenchymal stem cells - Che-Yi Chang; Ana Elena Aviña; Cheng-Jen Chang; Long-Sheng Lu; Yi-Yong Chong; Tzu Ying Ho; Tzu-Sen Yang (Journal of Photochemistry and Photobiology B: Biology, 2024)

Silicate melt immiscibility as the cause of large-scale rare-metal mineralization in a peralkaline granite system: The case of the Baerzhe deposit in NE China - Hui-Min Su; Shao-Yong Jiang; Tao Jin; Yu-Ying Che; Xin-You Zhu (Lithos, 2024)

Chlorpyrifos-induced suppression of the antioxidative defense system leads to cytotoxicity and genotoxicity in macrophages - Yin-Che Lu; Chen-Yu Chiang; Shih-Pin Chen; Yu-Wei Hsu; Wen-Ying Chen; Chun-Jung Chen; Yu-Hsiang Kuan; Sheng-Wen Wu (Environmental Toxicology and Pharmacology, 2024)

Characteristics and impacts of fine particulates from the largest power plant plume in Taiwan - Ming-Tung Chuang; Charles C.-K Chou; Chung-Te Lee; Ja-Huai Lee; Wei-Che Lin; Chuan-Yao Lin; Wei-Nai Chen; Yi-Ying Chen; Kai-Hsien Chi (Atmospheric Pollution Research, 2024)

Correction to: Novel FOXP2 variant associated with speech and language dysfunction in a Chinese family and literature review - Fengyu Che; Chenhao Li; Liyu Zhang; Chenxi Qian; Lidangzhi Mo; Benchang Li; Haibin Wu; Lifang Wang; Ying Yang (Journal of Applied Genetics, 2024)

Novel FOXP2 variant associated with speech and language dysfunction in a Chinese family and literature review - Fengyu Che; Chenhao Li; Liyu Zhang; Chenxi Qian; Lidangzhi Mo; Benchang Li; Haibin Wu; Lifang Wang; Ying Yang (Journal of Applied Genetics, 2024)

An effective strategy for improving the freeze-drying survival rate of Lactobacillus curvatus and its potential protective mechanism - Xiao-min Li; Lie-hua Che; Ying Wu; Cong Li; Bao-cai Xu (Food Bioscience, 2024)

N atoms regulate heterogeneous crystal phase engineering of mesoporous magnetic FexN nanofibers to promote electromagnetic wave dissipation of magnetic composite aerogel absorbers - Wanjia Li; Wangchang Li; Zengbao Ma; Yue Kang; Ting Zou; Yu Lei; Yao Ying; Wenbo Xiang; Jing Yu; Jingwu Zheng; Liang Qiao; Juan Li; et al. (Chemical Engineering Journal, 2024)

Relationship between night shift and sleep problems, risk of metabolic abnormalities of nurses: a 2 years follow-up retrospective analysis in the National Nurse Health Study (NNHS) - Heli Zhang; Jingpin Wang; Siwei Zhang; Sumei Tong; Jinping Hu; Ying Che; Lin Zhuo; Peng Wang; Rongmei Geng; Yujie Zhou; Panfeng Wang; Siyan Zhan; et al. (International Archives of Occupational and Environmental Health, 2023)
Background and purpose Efforts to improve nurses’ physical and mental health are critical to ensuring the safety and quality of the healthcare system. Long-term studies targeting the relevancy of nurses’ occupation characteristics with health conditions remain insufficient. This study aimed to examine the relationship between nurses’ night shift and sleep problems and metabolic abnormalities risk. Methods This study was a part of the National Nurse Health Study, an ambispective cohort study in China, in 2021. Based on an integration physical examination data system, this study carried out a retrospective analysis of 730 nurses from 2018 to 2020 and combined with a questionnaire survey in 2021. The STROBE guidelines were adopted for reporting. Results In the 23 (23.0, 24.0) months follow-up, higher night shift load was associated with more sleep problems such as shortened sleep duration, sleep disorders, poor sleep quality, and sleep deprivation. Moreover, night shift load was associated with chronic diseases risk factors, increasing body mass index and body fat, with more night shift density, increasing the occurrence of low levels of high-density lipoprotein cholesterol, high triglyceride, triglyceride/high-density lipoprotein cholesterol ratio, and serum uric acid. Conclusion The night shift load has become an occupational health concern, contributing to chronic diseases relevant metabolic risk factors and negative influence on sleep health. Focus on the strategies to improve the sleep quality of nurses undergoing night shift work, optimize work scheduling and ongoing monitor the relevant risk factors are essential to enhance the stability and well-being of the nursing workforce. Clinical Trials registration information: NCT04572347, on October 1, 2020. https://www.clinicaltrials.gov/ct2/show/NCT04572347

Elemental sulfur-driven autotrophic denitrification process for effective removal of nitrate in mariculture wastewater: Performance, kinetics and microbial community - Lu Wang; Jun Liu; Yongfu Li; Zhihao Liu; Long Zhang; Hong Che; Hongwu Cui; Ying Zhang (Chemosphere, 2023)

Strong variation of near-surface seismic anisotropy in Taiwan and its geological implications - Hsin-Yu Lee; Yuancheng Gung; Li-Wei Chen; Wen-Shan Chen; Ying-Nien Chen; Sheng-Jyun Cai; Hui-Chu Chen; Che-Wei Liao (Earth and Planetary Science Letters, 2023)

Synchronous regulation of Schottky/p-n dual junction in Prussian blue-derived Janus heterostructures: A path to ultrafast long life potassium ion batteries - Shou-Shan Mai; Kai-Yuan Hsiao; Yi-Chun Yang; Ying-Rui Lu; Ming-Yen Lu; Yi-Yen Hsieh; Che-Bin Chang; Hsing-Yu Tuan (Chemical Engineering Journal, 2023)

Growth-promoting and low-salt adaptation responses boosted by spermidine in Strombidium parasulcatum, a marine bacteriovorous ciliate potentially applied to live feeds for marine larviculture - Hung-Yun Lin; Bo-Ying Su; Nodali Ndraha; Sheng-Fang Tsai; Kuo-Ping Chiang; Hsin-Yun Liu; Yong-Ting Kang; Wei-Yu Yeh; Che-Chia Tsao; Yi-Min Chen; Hsin-I Hsiao; Han-Jia Lin (Aquaculture, 2023)

Propineb induced notochord deformity, craniofacial malformation, and osteoporosis in zebrafish through dysregulated reactive oxygen species generation - Wei Yuan; Ying Hu; Chen Lu; Jun Zhang; Ye Liu; Xinran Li; Kun Jia; Yong Huang; Zekun Li; Xiaomei Chen; Fei Wang; Xiaokun Yi; et al. (Aquatic Toxicology, 2023)

Tracing the future of epidemics: Coincident niche distribution of host animals and disease incidence revealed climate‐correlated risk shifts of main zoonotic diseases in China - Bo Cao; Chengke Bai; Kunyi Wu; Ting La; Yiyang Su; Lingyu Che; Meng Zhang; Yumeng Lu; Pufan Gao; Jingjing Yang; Ying Xue; Guishuang Li (Global Change Biology, 2023)
Climate has critical roles in the origin, pathogenesis and transmission of infectious zoonotic diseases. However, large‐scale epidemiologic trend and specific response pattern of zoonotic diseases under future climate scenarios are poorly understood. Here, we projected the distribution shifts of transmission risks of main zoonotic diseases under climate change in China. First, we shaped the global habitat distribution of main host animals for three representative zoonotic diseases (2, 6, and 12 hosts for dengue, hemorrhagic fever, and plague, respectively) with 253,049 occurrence records using maximum entropy (Maxent) modeling. Meanwhile, we predicted the risk distribution of the above three diseases with 197,098 disease incidence records from 2004 to 2017 in China using an integrated Maxent modeling approach. The comparative analysis showed that there exist highly coincident niche distributions between habitat distribution of hosts and risk distribution of diseases, indicating that the integrated Maxent modeling is accurate and effective for predicting the potential risk of zoonotic diseases. On this basis, we further projected the current and future transmission risks of 11 main zoonotic diseases under four representative concentration pathways (RCPs) (RCP2.6, RCP4.5, RCP6.0, and RCP8.5) in 2050 and 2070 in China using the above integrated Maxent modeling with 1,001,416 disease incidence records. We found that Central China, Southeast China, and South China are concentrated regions with high transmission risks for main zoonotic diseases. More specifically, zoonotic diseases had diverse shift patterns of transmission risks including increase, decrease, and unstable. Further correlation analysis indicated that these patterns of shifts were highly correlated with global warming and precipitation increase. Our results revealed how specific zoonotic diseases respond in a changing climate, thereby calling for effective administration and prevention strategies. Furthermore, these results will shed light on guiding future epidemiologic prediction of emerging infectious diseases under global climate change.

Two genes related to apoptosis in the hepatopancreas of juvenile prawn, Macrobrachium nipponense: Molecular characterization and transcriptional response to nanoplastic exposure - Yiming Li; Xinglin Du; Wen Li; Qichen Jiang; Yucong Ye; Ying Yang; Xingguo Liu; Yunlong Zhao; Xuan Che (Science of The Total Environment, 2023)

Andrographolide exerts anti-respiratory syncytial virus activity by up-regulating heme oxygenase-1 independent of interferon responses in human airway epithelial cells - Siyi Che; Na Zhou; Ying Liu; Jun Xie; Enmei Liu (Molecular Biology Reports, 2023)

Evaluation of the antimicrobial mechanism of biogenic selenium nanoparticles against Pseudomonas fluorescens - Ying Xu; Ting Zhang; Jiarui Che; Jiajia Yi; Lina Wei; Hongliang Li (Biofouling, 2023)

A low-cost eco-friendly fast drug extraction (FaDEx) technique for environmental and bio-monitoring of psychoactive drug in urban water and sports-persons’ urine samples - Swapnil Gurrani; Karthikeyan Prakasham; Jess Lim Zii Ying; Jentaie Shiea; Yi-Jia Ku; Yu-Chia Lin; Po-Chin Huang; Gangadhar Andaluri; Kung-Che Lee; Vinoth Kumar Ponnusamy (Environmental Research, 2023)

Using recoverable sulfurized magnetic biochar for active capping to remediate multiple heavy metal contaminated sediment - Che-Jung Hsu; Yung-Hua Cheng; Adrienne Chung; Ying-Pin Huang; Yu Ting; Hsing-Cheng Hsi (Environmental Pollution, 2023)

Recycling and remanufacturing technology analysis of permanent magnet synchronous motor - Zheng Li; Pengju Wang; Shuai Che; Shenhui Du; Ying Li; Hexu Sun (Clean Technologies and Environmental Policy, 2022)

Total, bioavailable and free 25-hydroxyvitamin D are associated with the prognosis of patients with non-small cell lung cancer - Si-Min Peng; Na Yu; Jun Che; Jia-Ying Xu; Guo-Chong Chen; Da-Peng Li; Yu-Song Zhang; Li-Qiang Qin (Cancer Causes & Control, 2022)

Characterization and Anticancer Activity of a Folic Acid Conjugated and Cationic Peptide L-K6 Encapsulated Cancer-Targeting Liposomal Drug Delivery System - Ying Wang; Huan Xu; Bo Wang; Ruixue Wang; Che Wang; Dejing Shang (International Journal of Peptide Research and Therapeutics, 2022)

Experimental investigation and discrete element method simulation on mechanical properties and failure mechanism of polymer-stabilized sand - Wenyue Che; Jin Liu; Hongyang Li; Chengzong He; Yuxia Bai; Zezhuo Song; Ying Wang; Wei Qian; Zhihao Chen (Bulletin of Engineering Geology and the Environment, 2022)

Synergistic Therapy of Doxorubicin with Cationic Anticancer Peptide L-K6 Reverses Multidrug Resistance in MCF-7/ADR Cancer Cells In Vitro via P-glycoprotein Inhibition - Che Wang; Lili Huang; Ruojin Li; Ying Wang; Xiaoxue Wu; Dejing Shang (International Journal of Peptide Research and Therapeutics, 2021)

Resolving Transboundary Water Conflicts: Dynamic Evolutionary Analysis Using an Improved GMCR Model - Mengjie Yang; Kai Yang; Yue Che; Shiqiang Lu; Fengyun Sun; Ying Chen; Mengting Li (Water Resources Management, 2021)

Syndecan-3 contributes to the regulation of the microenvironment at the node of Ranvier following end-to‑side neurorrhaphy: sodium image analysis - Chiung-Hui Liu; Yu-Chen Kuo; Che-Yu Wang; Chao-Chun Hsu; Ying-Jui Ho; Yun-Chi Chiang; Fu-Der Mai; Wei-Jhih Lin; Wen-Chieh Liao (Histochemistry and Cell Biology, 2021)

Effects of contrasting biochars on the leaching of inorganic nitrogen from soil - Ying Feng; Xing Yang; Bhupinder Pal Singh; Sanchita Mandal; Jia Guo; Lei Che; Hailong Wang (Journal of Soils and Sediments, 2020)

Using a numerical method to precisely evaluate the alpha angle in a hip image - Chung-Liang Lai; Wei-Min Chi; Ying-Jui Ho; Chien-Chung Lin; Hsiao-Che Lin; Chin-Liang Kuo; Jian-Horng Chen (Medical & Biological Engineering & Computing, 2019)

The Influence of Cellulosic Polymer’s Variables on Dissolution/Solubility of Amorphous Felodipine and Crystallization Inhibition from a Supersaturated State - Nian-Qiu Shi; Ying Jin; Yong Zhang; Xiao-Xia Che; Xiao Xiao; Gui-Hua Cui; Yu-Zhou Chen; Bo Feng; Zheng-Qiang Li; Xian-Rong Qi (AAPS PharmSciTech, 2019)

Biomimetic Placenta-Fetus Model Demonstrating Maternal–Fetal Transmission and Fetal Neural Toxicity of Zika Virus - Navein Arumugasaamy; Leila E. Ettehadieh; Che-Ying Kuo; Dominic Paquin-Proulx; Shannon M. Kitchen; Marco Santoro; Jesse K. Placone; Paola P. Silveira; Renato S. Aguiar; Douglas F. Nixon; John P. Fisher; Peter C. W. Kim (Annals of Biomedical Engineering, 2018)

Characterization and adsorption capacity of potassium permanganate used to modify activated carbon filter media for indoor formaldehyde removal - Shih-Cheng Hu; Ying-Chen Chen; Xin-Zhi Lin; Angus Shiue; Po-Hua Huang; Yen-Che Chen; Shu-Mei Chang; Chao-Heng Tseng; Bin Zhou (Environmental Science and Pollution Research, 2018)

Using nonlinear finite element models to analyse stress distribution during subluxation and torque required for dislocation of newly developed total hip structure after prosthetic impingement - Wei-Min Chi; Chien-Chung Lin; Ying-Jui Ho; Hsiao-Che Lin; Jian-Horng Chen (Medical & Biological Engineering & Computing, 2018)

Effects of feeding rates on growth, feed utilization, and body composition of juvenile Pseudobagrus ussuriensis - Xianyong Bu; Xuqiu Lian; Ying Zhang; Chenghui Yang; Cunhe Cui; Jianfang Che; Baibing Tang; Baohui Su; Qicun Zhou; Yuhong Yang (Aquaculture International, 2017)

Important Roles of Ring Finger Protein 112 in Embryonic Vascular Development and Brain Functions - Jen-Hui Tsou; Ying-Chen Yang; Ping-Chieh Pao; Hui-Ching Lin; Nai-Kuei Huang; Shih-Ting Lin; Kuei-Sen Hsu; Che-Ming Yeh; Kuen-Haur Lee; Chu-Jen Kuo; De-Ming Yang; Jiann-Her Lin; et al. (Molecular Neurobiology, 2017)

The Aggregation Pheromone of Phyllotreta striolata (Coleoptera: Chrysomelidae) Revisited - Franziska Beran; Guillermo H. Jiménez-Alemán; Mei-ying Lin; Yun-Che Hsu; Inga Mewis; Ramasamy Srinivasan; Christian Ulrichs; Wilhelm Boland; Bill S. Hansson; Andreas Reinecke (Journal of Chemical Ecology, 2016)

Disentangling the effects of isolation-by-distance and isolation-by-environment on genetic differentiation among Rhododendron lineages in the subgenus Tsutsusi - Chun-Lin Huang; Jui-Hung Chen; Chung-Te Chang; Jeng-Der Chung; Pei-Chun Liao; Jenn-Che Wang; Shih-Ying Hwang (Tree Genetics & Genomes, 2016)

Serum Uric Acid Levels and Diabetic Peripheral Neuropathy in Type 2 Diabetes: a Systematic Review and Meta-analysis - Shuai Yu; Ying Chen; Xu Hou; Donghua Xu; Kui Che; Changgui Li; Shengli Yan; Yangang Wang; Bin Wang (Molecular Neurobiology, 2016)

Cocaine Withdrawal Impairs mGluR5-Dependent Long-Term Depression in Nucleus Accumbens Shell Neurons of Both Direct and Indirect Pathways - Chiung-Chun Huang; Ying-Ching Liang; Cheng-Che Lee; Kuei-Sen Hsu (Molecular Neurobiology, 2015)

Theoretical Analysis of Total Hip Dislocation and Comparison of Hemispherical Cup and Newly Developed Cup - Hsiao-Che Lin; Wei-Min Chi; Ying-Jui Ho; Chien-Chung Lin; Jian-Horng Chen (Journal of Medical and Biological Engineering, 2015)

Alteration of ankle kinematics and muscle activity during heel contact when walking with external loading - Sheng-Che Yen; Gregory M. Gutierrez; Ying-Chih Wang; Patrick Murphy (European Journal of Applied Physiology, 2015)

Oxidative stress, apoptosis, and cell cycle arrest are induced in primary fetal alveolar type II epithelial cells exposed to fine particulate matter from cooking oil fumes - Ying Liu; Yan-Yan Chen; Ji-Yu Cao; Fang-Biao Tao; Xiao-Xia Zhu; Ci-Jiang Yao; Dao-Jun Chen; Zhen Che; Qi-Hong Zhao; Long-Ping Wen (Environmental Science and Pollution Research, 2015)

Establishment and maintenance of a standardized glioma tissue bank: Huashan experience - Abudumijiti Aibaidula; Jun-feng Lu; Jin-song Wu; He-jian Zou; Hong Chen; Yu-qian Wang; Zhi-yong Qin; Yu Yao; Ye Gong; Xiao-ming Che; Ping Zhong; Shi-qi Li; et al. (Cell and Tissue Banking, 2015)

Erratum to: Maternal exposure to fine particulate matter (PM2.5) and pregnancy outcomes: a meta-analysis - Xiaoxia Zhu; Ying Liu; Yanyan Chen; Cijiang Yao; Zhen Che; Jiyu Cao (Environmental Science and Pollution Research, 2015)

Maternal exposure to fine particulate matter (PM2.5) and pregnancy outcomes: a meta-analysis - Xiaoxia Zhu; Ying Liu; Yanyan Chen; Cijiang Yao; Zhen Che; Jiyu Cao (Environmental Science and Pollution Research, 2015)

Preparation and application of collagen scaffold-encapsulated silver nanoparticles and bone morphogenetic protein 2 for enhancing the repair of infected bone - Chang-ying Sun; Yan-jun Che; Shi-jin Lu (Biotechnology Letters, 2015)

Experiments on channel evolution due to dam removal in Taiwan - Hsiao-Wen Wang; Ying-Che Cheng; Chung-Yi Lin (Journal of Mountain Science, 2014)

A cellular response protein induced during HSV-1 infection inhibits viral replication by interacting with ATF5 - LianQiu Wu; XueMei Zhang; YanChun Che; Ying Zhang; SongQing Tang; Yun Liao; RuiXiong Na; XiangLin Xiong; LongDing Liu; QiHan Li (Science China Life Sciences, 2013)

Functional transient receptor potential canonical type 1 channels in human atrial myocytes - Yan-Hui Zhang; Hui-Jun Wu; Hui Che; Hai-Ying Sun; Lik-Cheung Cheng; Xin Li; Wing-Kuk Au; Hung-Fat Tse; Gui-Rong Li (Pflügers Archiv - European Journal of Physiology, 2013)

Effects of design parameters of total hip components on the impingement angle and determination of the preferred liner skirt shape with an adequate oscillation angle - Hsiao-Che Lin; Wei-Min Chi; Ying-Jui Ho; Jian-Horng Chen (Medical & Biological Engineering & Computing, 2013)

Risk factors for primary lung cancer among never smokers by gender in a matched case–control study - Yen-Li Lo; Chin-Fu Hsiao; Gee-Chen Chang; Ying-Huang Tsai; Ming-Shyan Huang; Wu-Chou Su; Yuh-Min Chen; Che-Wei Hsin; Chin-Hao Chang; Pan-Chyr Yang; Chien-Jen Chen; Chao A. Hsiung (Cancer Causes & Control, 2013)

Helicobacter pylori HP0876 is Dispensable for Heme–Iron Acquisition but Attenuates Bacterial Adherence to Gastric Epithelial Cells - Tao Liu; Yun Shi; Xiao-fei Liu; Ying Guo; Xu-hu Mao; Che Tan; Yuan Zhuang; Liu-sheng Peng; Jin-yu Zhang; Quan-ming Zou (Current Microbiology, 2012)

Reversine, a 2,6-disubstituted Purine, as an Anti-cancer Agent in Differentiated and Undifferentiated Thyroid Cancer Cells - Shih-Che Hua; Tien-Chun Chang; Hau-Ren Chen; Chieh-Hsiang Lu; Yi-Wen Liu; Shu-Hsin Chen; Hui-I Yu; Yi-Ping Chang; Ying-Ray Lee (Pharmaceutical Research, 2012)

Induction of primitive pigment cell differentiation by visible light (helium–neon laser): a photoacceptor-specific response not replicable by UVB irradiation - Cheng-Che E. Lan; Shi-Bei Wu; Ching-Shuang Wu; Yi-Chun Shen; Tzu-Ying Chiang; Yau-Huei Wei; Hsin-Su Yu (Journal of Molecular Medicine, 2012)

Numerical experiments investigating the orographic effects on a heavy rainfall event over the northwestern coast of Taiwan during TAMEX IOP 13 - Pay-Liam Lin; Yi-Leng Chen; Ching-Sen Chen; Che-Ling Liu; Ching-Ying Chen (Meteorology and Atmospheric Physics, 2011)

Passenger thermal perceptions, thermal comfort requirements, and adaptations in short- and long-haul vehicles - Tzu-Ping Lin; Ruey-Lung Hwang; Kuo-Tsang Huang; Chen-Yi Sun; Ying-Che Huang (International Journal of Biometeorology, 2010)

Monoamine oxidase A gene polymorphisms and enzyme activity associated with risk of gout in Taiwan aborigines - Hung-Pin Tu; Albert Min-Shan Ko; Shu-Jung Wang; Chien-Hung Lee; Rod A. Lea; Shang-Lun Chiang; Hung-Che Chiang; Tsu-Nai Wang; Meng-Chuan Huang; Tsan-Teng Ou; Gau-Tyan Lin; Ying-Chin Ko (Human Genetics, 2010)

Chronic treatment with monoamine oxidase-B inhibitors decreases cocaine reward in mice - Ming-Che Ho; Chianfang G. Cherng; Yen-Ping N. Tsai; Chih-Yuan Chiang; Jia-Ying Chuang; Shu-Fang Kao; Lung Yu (Psychopharmacology, 2009)

Baicalein attenuates intimal hyperplasia after rat carotid balloon injury through arresting cell-cycle progression and inhibiting ERK, Akt, and NF-κB activity in vascular smooth-muscle cells - Chieh-Yu Peng; Shiow-Lin Pan; Ying-Wen Huang; Jih-Hwa Guh; Ya-Ling Chang; Che-Ming Teng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2008)

Identification and characterization of two uvrA genes of Xanthomonas axonopodis pathovar citri - Che-Hung Shen; Ying-Chieh Chiang; Chien-Hsiu Hsu; Mei-Kwei Yang (Molecular Genetics and Genomics, 2007)

Phylogeography of Trochodendron aralioides (Trochodendraceae) in Taiwan and its adjacent areas - Shing‐Fan Huang; Shih‐Ying Hwang; Jenn‐Che Wang; Tsan‐Piao Lin (Journal of Biogeography, 2004)
Aim This paper described current phylogeographical patterns of chloroplastic DNA variation of Trochodendron aralioides , a temperate tree species, and inferred its possible refugium in Taiwan. This information was compared with the known phylogeographical pattern of subtropical tree species. Location A total of 24 populations were sampled including 20 from Taiwan, two each from the Ryukyus and Japan. Methods A haplotype network was constructed by computer program TCS, various parameters of genetic diversity were calculated and neutrality was tested by computer program DnaSP. To examine the similarity of genetic structure among populations, a maximum parsimony tree was reconstructed by computer program PAUP*. The results of isozyme of T. aralioides from a previous publication were incorporated into this study to infer the phylogeographical history. Results Nine haplotypes according to six substitutions, two indels and one inversion of the two cpDNA intergenic spacer fragments ( pet G‐ trn P and pet A‐ psb J) of T. aralioides were recognized. Genetic structure of the population of Japan is totally different from those of Taiwan and the Ryukyus. In Taiwan, the genetic structure was differentiated among populations revealed by G st = 0.700 and N st = 0.542, and the population genetics was clearly spatially structured. Two population groups were recognized. The first group was distributed islandwide and extended to the Ryukyus. The second group contained five of the seven known haplotypes, and was restricted to the area between latitude 24°46′ and 24°06′ N. Conclusions In Taiwan, north‐central area between latitude 24°46′ and 24°06′ N is potentially a refugium during the last glaciations. This finding is contradicted to subtropical species as Cyclobalanopsis glauca .

Hydrogen peroxide enhanced inron-induced injury in isolated heart and ventricular cardiomyocyte in rats - Ying Ying Che Chen; Kwok Pin Ho; Qiang Xia; Zhong Ming Qian (Molecular and Cellular Biochemistry, 2002)

Natural Frequency Analysis of Periodontal Conditions in Human Anterior Teeth - Haw-Ming Huang; Sheng-Yang Lee; Ching-Ying Yeh; Mao-Sheng Wang; Wei-Jen Chang; Che-Tong Lin (Annals of Biomedical Engineering, 2001)